Efectos generados por el Covid-19 en los hoteles y restaurantes de Trujillo - Sánchez Bellido, Luz Violeta (2023)
This thesis called Effects generated by Covid-19 in Trujillo hotels and restaurants, sought to identify the economic and social effects that the Covid-19 pandemic has generated in Trujillo hotels and restaurants throughout this time of crisis._x000D_ This research addressed exclusive data from three-star lodging establishments and three-star restaurant establishments, both in the district of Trujillo. It was learned that the economic effects on these companies due to the pandemic were the closure of their premises, the null and little economic income in them and the unemployment of many workers as effects. Likewise, an analysis was made of the social effects caused by the pandemic, which were the stress of the workers and those in charge of managing these companies (owners and administrators), and the change in the social interaction of the worker-client in that period. All these data were collected from 69 lodging establishments and 3 catering establishments registered in the National Directory of Tourist Service Providers of the Mincetur._x000D_ Regarding the research methodology, it was based on two methods, the ethnographic and the analytical-synthetic, the techniques applied were the interview, the survey, the graphic record, the signing, and direct observation. Likewise, the instruments used were the interview guide, the survey guide, the textual cards and the photographic camera. All these tools helped to fulfill the study of the research variables.